Exploring the decline in health index of the Qarhan salt lake region in Qinghai Province, China: A 40-year assessment - Pengfei Ji; Qian Shen; Ru Wang; Yue Yao; Bing Zhang; Wenting Xu; Yuting Zhang; Wenqi Kou; Wenxin Li (Ecological Indicators)
Salt lakes are unique bodies of water with specific environmental conditions that make sampling challenging, and there is a lack of established health assessment methods. Previous research has focused on the health status of freshwater lakes in urban and rural areas; however, the health of freshwater lakes is not directly comparable to that of salt lakes. Therefore, past studies on lake health evaluations cannot be applied to salt lakes. In this study, we develop a Salt Lake Health Index (SLHI), suitable for assessing salt lake regions affected by human activities, using the Analytic Hierarchy Process and remote sensing technology. The SLHI is a composite index that reflects the overall health status of salt lakes. Located in Qinghai Province, China, the Qarhan Salt Lake is the largest salt lake in China, consisting of four lakes: Dabuxun, South Hobson, North Hobson, and Se-nie. We evaluate the health of this region over nearly four decades (1990, 2000, 2010, 2020). The results indicate a decline in the Salt Lake Health Index (SLHI) from 83.16 in 1990 to 44.54 in 2020. Notably, the period from 2010 to 2020 experienced the most rapid decline, with a reduction of 19.43. The primary factors influencing the SLHI include shoreline and landscape changes and land use variations. The health assessment method established in this study will enhance understanding of salt lake health, promoting the sustainable development of salt lake resources and their ecological functions.